2019
DOI: 10.1674/0003-0031-181.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Wildfire Burn Severity, Cavity-Nesting Bird Assemblages, and Habitat in an Eastern Ponderosa Pine Forest

Abstract: Historically, eastern ponderosa pine (Pinus ponderosa) forests were described as sparse patches of old-growth trees maintained by frequent, low-severity fires; however, in recent decades, there have been a number of large mixed-severity wildfires throughout the range of these forests. Wildlife responses to severe fire disturbance in eastern ponderosa pine forests are not well understood. Our study investigates how cavity-nesting bird species in an eastern ponderosa pine forest are impacted by burn severity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…Flora and fauna species richness and biomass decrease when snags and coarse woody debris are removed from a landscape [13,17]. In eastern ponderosa pine, coarse woody debris cover has been shown to be an important factor in determining cavity-nesting bird community composition [75]. Fallen trees can provide important nesting habitat, predator cover, and foraging opportunities [76,77].…”
Section: Wildlife Community and Habitat Characteristicsmentioning
confidence: 99%
“…Flora and fauna species richness and biomass decrease when snags and coarse woody debris are removed from a landscape [13,17]. In eastern ponderosa pine, coarse woody debris cover has been shown to be an important factor in determining cavity-nesting bird community composition [75]. Fallen trees can provide important nesting habitat, predator cover, and foraging opportunities [76,77].…”
Section: Wildlife Community and Habitat Characteristicsmentioning
confidence: 99%
“…in other studies that show fire severity affects snag retention, density, and habitat variation and thus presence of cavity nesters (Keele et al, 2019;Saab et al, 2004). Conversely, herbivores did not have as strong of a negative response to high severity fire.…”
Section: Discussionmentioning
confidence: 59%
“…Although snag densities only differed between burned versus unburned, the unique bird and woody plant communities among fire severities indicate other material legacies persist across a fire severity gradient and continue to influence biotic communities. For instance, in the same system, Keele et al () found that, when comparing multiple forest stand structural characteristics, coarse woody debris was the strongest indicator of cavity‐nesting bird community composition 27‐year post‐fire. This difference in structure may explain some disparities between our study and others in bird‐fire severity associations: for example, Hairy Woodpeckers and Western Wood Pewees were more strongly associated with higher burn severities in other studies than in ours (Fontaine & Kennedy, ; Smucker, Hutto, & Steele, ).…”
Section: Discussionmentioning
confidence: 99%